Analyzing and Modelling Pharmacy Queue System Using Simulation - Argaditia Mawadati; Mega Inayati Rif’ah; Lalang Pramuditya (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
Waiting time and queue length at the pharmacy are very influential for customer satisfaction. A hospital’s pharmacy which the object of this study has a long waiting time. The aim of this study is to analyzing and modelling pharmacy queue using simulation method, then simulating a new scenario as an effort to improve the queue system. The improvement scenario was simulated by adding one server at payment locket. The simulation was carried out using empirical and theoretical approaches. The analysis was conducted based on the results of the simulation. Results showed that based on validity test can be concluded that the simulation using empirical and theoretical approach do not differ significantly from the real system. And based on the experiment from improvement scenario it showed that the addition of payment server did not show a significant difference from origin situation, the waiting time only decreased by approximately 30 minutes.